Lobbying in Polish law and practice - Kubiak, Anna (Annales. Etyka w Życiu Gospodarczym, 2019)
This article presents both the legal regulations concerning lobbying in Poland and an evaluation of lobbying practices. It refers to the results of the sociological research conducted among the members of the Polish Parliament, professional lobbyists and journalists who cover parliamentary issues. The research was conducted in cooperation with the Stefan Batory Foundation’s Anti-Corruption Programme from May to July 2008.